Partial Purification and Characterisation of Pectinase Produced by Aspergillus niger LFP-1 Grown on Pomelo Peels as a Substrate - Mohd Taufiq Mat Jalil; Darah Ibrahim (Tropical Life Sciences Research, 2021)
In the present study, pectinase was produced by local fungal isolate, Aspergillus niger LFP-1 grown on pomelo peels as a sole carbon source under solid-state fermentation. The purification process begins with the concentration of crude enzyme using ammonium sulfate precipitation and followed by purification using anion-exchange column chromatography (DEAE-Sephadex) and subsequently using gel filtration column chromatography (Sephadex G-100). On the other hand, the molecular weight of the purified enzyme was determined through SDS-PAGE. The findings revealed the crude enzyme was purified up to 75.89 folds with a specific activity of 61.54 U/mg and the final yield obtained was 0.01%. The molecular mass of the purified pectinase was 48 kDa. The optimum pH and temperature were 3.5 and 50oC, respectively. This enzyme was stable at a range of pH 3.5 to 4.5 and a relatively high temperature (40-50oC) for 100 minutes. The Km and Vmax were found to be 3.89 mg/ml and 1701 U/mg, respectively. Meanwhile, pectin from citrus fruit and the metal ion (Co2+) were the best substrate and inducer to enhance pectinase yield, respectively.